Knowledge and attitudes of AIDS education workers in Barbados - abstract - Walrond, Errol R.
Two workshops were held for AIDS education workers, which were intended to update them on information and to provide a forum for discussion of issues pertinent to the education effort on AIDS in Barbados. A pre-workshop questionnaire was administered to determine the knowledge and attitudes of the education workers about HIV/AIDS and some of the issues that arise in public fora. Analysis of the results showed that participants, with few exceptions, were clear about the risks of transmission by anal and vaginal sex, but were less certain about transmission by the oral route, by accidents, and by breast feeding. Participants were knowledgeable about the ways in which HIV affects a person, both before and with the onset of AIDS. On the other hand, there were some significant defects in knowledge on AIDS statistics and on the haematological effects, including the nature of the test, amongst the non-physician participants. Between 10 and 20 percent of respondents did not answer the questions related to legal and ethical issues, but those who answered had a grasp of the issues related to the right to know and prohibition from jobs. Significantly, more men and doctors were in favour of the ready availability of condoms to youth, otherwise there was general support (60-90 percent) for the provision of condoms in a wide variety of situations, including prisons, but not in schools where the respondents were evenly split. It is concluded that there is justification for ensuring that AIDS educators be kept up to date on technical matters, and that they should have a forum to discuss and clarify issues of concern to the public
Keywords: Health personnel